Kinesiophobia and related factors in adult patients with familial mediterranean fever - Saka, Seda; Çetinkaya, İrem; Günaydın, Elif İrem; Çetinkaya, Ayşenur; Yavuzer, Melek Güneş (Georg Thieme Verlag, 2023)
Objective Kinesiophobia is a common problem in patients with rheumatic diseases and can cause physical inactivity, social isolation, disability, and poor quality of life. This study aimed to evaluate kinesiophobia and associated factors in patients with familial Mediterranean fever (FMF). Methods A total of 38 patients diagnosed with FMF volunteered to participate in the study. All patients were assessed using the Tampa Kinesiophobia Scale (TKS), the International Physical Activity Questionnaire (IPAQ), the Fatigue Severity Scale (FSS), and the Hospital Anxiety and Depression Scale (HADS). Results Thirty-three (86.8%) of the patients had TKS scores over 37, indicating high levels of kinesiophobia. The TKS score was positively correlated with the HADS depression score (r=0.530; p=0.001) and the FSS score (r=0.340; p=0.035) but was not significantly associated with age (r=0.102; p=0.543), disease duration (r=-0.110; p=0.511), body mass index (r=0.283; p=0.085), the HADS anxiety score (r=0.306; p=0.061), or the IPAQ score (r=-0.097; p=0.563). Conclusions Our sample of adult FMF patients showed high levels of kinesiophobia associated with fatigue and depression. Treatments focusing on kinesiophobia in FMF patients could help to increase the effectiveness of rehabilitation.
Keywords: Familial Mediterranean Fever; Kinesiophobia; Rehabilitation; Familiärem Mittelmeerfieber; Kinesiophobie; Rehabilitation